Management of Headmaster Academic Supervision in Improving Teachers’ Performance At Madrasah Ibtidaiyah (MI) Dasussalam Ciamis - Ibrahim, Tatang; Kusoy, Kusoy (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The success of an educational institution is the management that carried out by the headmaster as the highest leader in the institution. The headmaster as the manager has the authority to carry out supervision to improve teachers’ performance. The aim of this research is to find out the academic supervision program, supervision implementation, supervision techniques, follow-up supervision results, and inhibitory factors in the implementation of academic supervision by the headmaster of MI Darussalam Ciamis. The research method used is descriptive qualitative by applying interviews, observations and documentation as data collection techniques. The subject of this study is the headmaster and teachers of MI Darussalam, there are 20 participants. The results of this study are: 1) Academic supervision program is oriented towards teachers’ guidance to improve teachers’ performance through discussions with teachers; 2) The implementation of academic supervision has several stages, the first is the initial planning, the second is the implementation of observation, and the final stage is the learning process becomes effective; 3) The techniques used by the headmaster are individual techniques, group techniques and clinical supervision; 4) The follow-up of this supervision is the provision of assistance and guidance to teachers who are still having difficulty in carrying out their duties as teachers, improving teachers’ professionalism through teachers’ meeting activities and attending training; 5) The inhibition factor in the implementation of academic supervision is the low competence of some supervisors appointed due to lack of human resources.